2011
DOI: 10.1007/s10964-011-9675-1
|View full text |Cite
|
Sign up to set email alerts
|

Racial Pride and Religiosity among African American Boys: Implications for Academic Motivation and Achievement

Abstract: The persistent underachievement among African American boys has led to increased empirical inquiry, yet little research considers within-group variation in achievement nor positive youth characteristics that help explain positive achievement outcomes. This study conceptualized culturally-based factors (racial pride and religiosity) as adolescent assets that would promote African American boys' achievement and also enhance positive effects of other youth assets (positive educational utility beliefs) on achievem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 64 publications
0
28
0
Order By: Relevance
“…In the current study, we will explore private regard, a construct conceptualized by Sellers, Smith, et al (1998) in their racial identity framework, defined as individuals' affective feelings about their racial group membership, including an awareness of and pride in the group's heritage and societal contributions. Overall, African American adolescents endorsing high private regard have been found to have higher academic motivation and performance than African Americans with low private regard (e.g., Butler-Barnes, Williams, & Chavous, 2012;Wong, Eccles, & Sameroff, 2003). In addition, McCreary, Slavin, and Berry (1996) found that African American adolescents who endorsed less positive attitudes about African Americans had more problematic behavior.…”
Section: African American Adolescents' Academic and Cultural Assetsmentioning
confidence: 99%
“…In the current study, we will explore private regard, a construct conceptualized by Sellers, Smith, et al (1998) in their racial identity framework, defined as individuals' affective feelings about their racial group membership, including an awareness of and pride in the group's heritage and societal contributions. Overall, African American adolescents endorsing high private regard have been found to have higher academic motivation and performance than African Americans with low private regard (e.g., Butler-Barnes, Williams, & Chavous, 2012;Wong, Eccles, & Sameroff, 2003). In addition, McCreary, Slavin, and Berry (1996) found that African American adolescents who endorsed less positive attitudes about African Americans had more problematic behavior.…”
Section: African American Adolescents' Academic and Cultural Assetsmentioning
confidence: 99%
“…Further, spirituality has been associated with a range of emotional protective processes, including happiness, hope, faith, optimism, strength, confidence, forgiveness, trust, and meaning (Mattis, 2001). Church involvement promotes positive behavior and developmental outcomes through its impact on moral development, racial pride, and self-esteem (Butler- Barnes, Williams, & Chavous, 2012). Spirituality coupled with high levels of family connections and kinship support are major protectors for dissuading Black adolescents from initiating substance use, with lasting effects to avert binge drinking as they transition into young adulthood (Stevens-Watkins & Rostosky, 2010).…”
Section: Racial Socialization and Racial Identitymentioning
confidence: 99%
“…Intrinsic religiosity refers to private religious practices such as prayer that demonstrate devotion to the divine (Levin et al., ). Adolescents may conceive of prayer as a way to cope with SLEs, and religious AA adolescents often report that they pray to receive divine assistance in their academics (Butler‐Barnes, Williams, & Chavous, ), treatment of physical illness (Davey, Tubbs, Kissil, & Niño, ), and their relational life (e.g., peer–sibling relations; McHale, Kim, Whiteman, & Crouter, ).…”
Section: The Meaning Of Religiositymentioning
confidence: 99%